Efficiency, Stability, and Productivity on Indonesian Islamic Insurance Industry - Solihah Sari Rahayu; Abrista Devi (Islamic Social Finance, 2023)
This study attempts to analyze the productivity level of Takaful industry in Indonesia, both in terms of changes of its efficiency and also its technological. There are two things that are calculated in Malmquist index measurement that is catch-up effect and frontier shift effect. Findings from the results are very interesting. The average value of the overall efficiency of Takaful industry in Indonesia is relatively medium at 77.8%, while the mean standard deviation is 0.17. This indicates the enough good performance of Takaful industry in Indonesia. In general, there has been an increase in the level of productivity of Takaful institutions in Indonesia in the period 2016 to 2018, even though its very small. The increase in productivity growth (1.076) of Takaful institutions in Indonesia is generally caused by technological change (1.078) instead of changes in efficiency (0.998). Thus the service of Takaful institutions is needed which is more innovative in relation to the development of technology in the future.